The interplay between (electro)chemical and (chemo)mechanical effects in the cycling performance of thiophosphate-based solid-state batteries. (1st March 2022) - Teo, Jun Hao; Strauss, Florian; Walther, Felix; Ma, Yuan; Payandeh, Seyedhosein; Scherer, Torsten; Bianchini, Matteo; Janek, Jürgen; Brezesinski, Torsten
Abstract: Solid-state batteries (SSBs) are a promising next step in electrochemical energy storage but are plagued by a number of problems. In this study, we demonstrate the recurring issue of mechanical degradation because of volume changes in layered Ni-rich oxide cathode materials in thiophosphate-based SSBs. Specifically, we explore superionic solid electrolytes (SEs) of different crystallinity, namely glassy 1.5Li2 S-0.5P2 S5 -LiI and argyrodite Li6 PS5 Cl, with emphasis on how they affect the cyclability of slurry-cast cathodes with NCM622 (60% Ni) or NCM851005 (85% Ni). The application of a combination of ex situ and in situ analytical techniques helped to reveal the benefits of using a SE with a low Young's modulus. Through a synergistic interplay of (electro)chemical and (chemo)mechanical effects, the glassy SE employed in this work was able to achieve robust and stable interfaces, enabling intimate contact with the cathode material while at the same time mitigating volume changes. Our results emphasize the importance of considering chemical, electrochemical, and mechanical properties to realize long-term cycling performance in high-loading SSBs. Video Abstract: Video Abstract: The interplay between (electro)chemical and (chemo)mechanical effects in the cycling performance of thiophosphate-based solid-state batteries